Mitochondrial Transfer Regulates Cell Fate Through Metabolic Remodeling in Osteoporosis. Issue 4 (11th December 2022) - Cai, Wenjin; Zhang, Jinglun; Yu, Yiqian; Ni, Yueqi; Wei, Yan; Cheng, Yihong; Han, Litian; Xiao, Leyi; Ma, Xiaoxin; Wei, Hongjiang; Ji, Yaoting; Zhang, Yufeng
Abstract: Mitochondria are the powerhouse of eukaryotic cells, which regulate cell metabolism and differentiation. Recently, mitochondrial transfer between cells has been shown to direct recipient cell fate. However, it is unclear whether mitochondria can translocate to stem cells and whether this transfer alters stem cell fate. Here, mesenchymal stem cell (MSC) regulation is examined by macrophages in the bone marrow environment. It is found that macrophages promote osteogenic differentiation of MSCs by delivering mitochondria to MSCs. However, under osteoporotic conditions, macrophages with altered phenotypes, and metabolic statuses release oxidatively damaged mitochondria. Increased mitochondrial transfer of M1‐like macrophages to MSCs triggers a reactive oxygen species burst, which leads to metabolic remodeling. It is showed that abnormal metabolism in MSCs is caused by the abnormal succinate accumulation, which is a key factor in abnormal osteogenic differentiation. These results reveal that mitochondrial transfer from macrophages to MSCs allows metabolic crosstalk to regulate bone homeostasis. This mechanism identifies a potential target for the treatment of osteoporosis. Abstract : The findings reveal a new pattern of cellular crosstalk in the bone marrow environment, with macrophages regulating bone metabolism crosstalk by transferring their mitochondria into mesenchymal stem cells. This study suggests that mitochondrial transfer may be a novel way to regulate homeostasis by enabling immune cells to regulate their local tissue environment.